Analysis of the Importance of Utilizing Research Instruments - Agus Salim; Nurmafitriyani Juita (al-Afkar, Journal For Islamic Studies, 2025)
Instruments play a crucial role in research. The importance of these instruments lies in generating data from the variables or focus of discussion by identifying their indicators. The research method used was a Systematic Literature Review (SLR). SLR, as a research method, aims to comprehensively discover and synthesize research addressing specific questions using organized, transparent, and replicable procedures. Through inclusion criteria for relevant studies, articles were further categorized based on study characteristics or moderating variables, namely: year of publication, keywords based on the topic, journal indexer, country of study, applied research methods, data collection tools, sample study groups, and data analysis techniques.